PREVALENCE AND ASSESSMENT OF ASSOCIATED RISK FACTORS OF EARLY CHILDHOOD CARIES IN RURAL OF KHEDA, GUJARAT - Nisarg S Raval,; Nirav R Rathod,; Rudra J Shah,; Viraj H Patel,; Jyoti S Mathur, (The Bioscan, 2025)
Aim: Goal of the present study was to survey the prevalence of early childhood caries and assess its risk factors in children from rural areas of Kheda, Gujarat. Methodology: Study sample comprised 433 children of both sexes from the age group of 2 to 6 years from 12 rural primary schools and Anganwadi’s of Kheda, Gujarat. The selection of the sample was random. A structured questionnaire was asked to children through their class teachers before conducting the examination. The form included information about their child’s basic personal details, parental occupational status and type of living, their dishes of interest, feeding habits, tooth-brushing habits, and awareness about dental treatment. Results: Study surveyed 433 children aged 2–6 years in rural Kheda, Gujarat, to assess the prevalence of early childhood caries (ECC) and its associated risk factors. The mean age of participants was 4.59 ± 0.97 years, with a median age of 5 years (IQR: 4–5). The overall prevalence of ECC was 33.3%, affecting 144 children, while 289 children remained caries-free. Conclusion: Cross-sectional study of 433 children aged two to six years from rural Kheda, Gujarat, highlights early childhood caries (ECC) as a significant oral health concern, with an overall prevalence of 33.3%.